1103 AN EVALUATION OF A GERIATRICIAN-LED ACUTE MEDICAL ADMISSION UNIT AT MORRISTON HOSPITAL, SWANSEA. (16th January 2023) - Yusoff, A; Davies, E A; Burberry, D J; Jones, N; Walters, C; Beynon Howells, C; Davies, D; Quinn, P
Abstract: Introduction: The medical intake at Morriston Hospital is accepted on two units; Rapid Assessment Unit (RAU) and Acute Medical Assessment Unit. Both were acute physician-led until July 2021 Method: (Phase 1). From July 2021, RAU became geriatrician-led (Phase 2). This evaluation concerns the performance of RAU. Phase 1 (Acute Physician-Led Unit) Between 01/08/2020-30/06/2021, there were 3102 admissions with a median length of stay (LOS) of 2 days on RAU. 37.2% of patients were discharged directly from the unit. (SBUHB data). A detailed analysis of 496 patients consecutively assessed between November 2020–January 2021 showed a median LOS on RAU of 1, 28.8% were discharged directly from RAU. Overall health board (HB) median LOS for the cohort was 7. In over 70 years, median LOS on RAU was 1, overall HB LOS 9. Phase 2 (Geriatrician-Led Unit) 1237 patients were assessed July-December 2021, with a median LOS of 2 days. 42.8% of patients were discharged from RAU. (SBUHB data). A detailed analysis of 566 patients consecutively assessed between September-November 2021 showed a median LOS on RAU of 2, 41.7% discharged directly from RAU. Overall HB median LOS for the entire cohort was 5. For the > 70 years, median LOS on RAU was 2, overall HB LOS was 7. Patient flow through assessment areas is dependent on the function of downstream medical wards. Mean LOS within medicine at Morriston increased 1.5 days between Phase 1 and Phase 2. Results: Acute geriatricians have delivered the 72hr LOS standard that SBUHB has set for assessment areas. The unit has achieved a reduction in overall LOS for the cohort of patients evaluated (p<.01), especially for the > 70 years (p=.007). Conclusion: This data supported a change in practice; RAU has taken a frailty specific intake since January 2022.